Potential Moderating Effects of Sex/Gender on the Acute Relative Reinforcing and Subjective Effects of Reduced Nicotine Content Cigarettes in Vulnerable Populations. Issue 6 (19th June 2019) - Streck, Joanna M; Davis, Danielle R; Pang, Raina D; Sigmon, Stacey C; Bunn, Janice Y; Bergeria, Cecilia L; Tidey, Jennifer W; Heil, Sarah H; Gaalema, Diann E; Hughes, John R; Stitzer, Maxine L; Reed, Ellaina; et al.
Abstract: Introduction: Reports in relatively healthy smokers suggest men are more sensitive than women to the subjective effects of reduced nicotine content cigarettes (RNCCs). We know of no reports examining sex differences in the relative reinforcing effects of RNCCs, an important outcome in assessing smoking's addiction potential. The aim of the present study is to address this gap by examining sex/gender differences on reinforcing effects while examining whether sex differences in subjective effects are discernible in vulnerable populations. Methods: Secondary analysis of a within-subject, double-blinded experiment examining acute effects of cigarettes varying in nicotine content (0.4, 2.4, 5.2, 15.8 mg/g) among 169 adult smokers with psychiatric conditions or socioeconomic disadvantage. Effects of dose, sex, and their interaction were examined on reinforcing (concurrent-choice and Cigarette Purchase Task [CPT] testing), and subjective effects (Cigarette Evaluation Questionnaire [CEQ] and craving/withdrawal ratings). Results: Reducing nicotine content decreased the relative reinforcing effects of smoking in concurrent-choice and CPT testing ( p 's < .05) with no significant effects of sex nor dose × sex/gender interactions. Reducing nicotine content decreased CEQ ratings with only a single significant effect of sex (higher Psychological Reward scores among women than men, p = .02) and no significant dose × sex/gender interactions. Results on craving/withdrawal paralleled those on the CEQ. Conclusions: Reducing nicotine content decreases the addiction potential of smoking independent of sex in populations highly vulnerable to smoking and addiction, with no indication that women are less sensitive to subjective effects of RNCCs or would benefit less from a policy reducing the nicotine content of cigarettes. Implications: A policy reducing the nicotine content of cigarettes has the potential to reduce the addiction potential of smoking across men and women who are especially vulnerable to smoking, addiction, and tobacco-related adverse health impacts.